Resistance to hypoxia-induced, BNIP3-mediated cell death contributes to an increase in a CD133-positive cell population in human glioblastomas in vitro - Kahlert, Ulf D.; Herold-Mende, Christel (Journal of neuropathology and experimental neurology, 2012)
Abstract: In addition to intrinsic regulatory mechanisms, brain tumor stemlike cells (BTSCs), a small subpopulation of malignant glial tumor-derived cells, are influenced by environmental factors. Previous reports showed that lowering oxygen tension induced an increase of BTSCs expressing CD133 and other stem cell-related genes and more pronounced clonogenic capacity in vitro. We investigated the mechanisms responsible for hypoxia-dependent induction of CD133-positive BTSCs in glioblastomas. We confirmed that cultures exposed to lowered oxygen levels showed a severalfold increase of CD133-positive BTSCs. Both the increase of CD133-positive cells and deceleration of the growth kinetics were reversible after transfer to normoxic conditions. Exposure to hypoxia induced BNIP3 (BCL2/adenovirus E1B 19-kDa protein-interacting protein 3)-dependent apoptosis preferentially in CD133-negative cells. In contrast, CD133-positive cells proved to be more resistant to hypoxia-induced programmed cell death. Application of the demethylating agent 5′-azacitidine resulted in an increase of BNIP3 expression levels in CD133-positive cells. Thus, epigenetic modifications led to their better survival in lowered oxygen tension. Moreover, the, hypoxia-induced increase of CD133-positive cells was inhibited after 5′-azacitidine treatment. These results suggest the possible efficacy of a novel therapy for glioblastoma focused on eradication of BTSCs by modifications of epigenetic regulation of gene expression.